THEORETICAL PRINCIPLES OF THE UNIFORM SOCIAL CONTRIBUTION AND ITS DISPLAY IN THE SYSTEM OF ACCOUNTING AND CONTROL OF CALCULATIONS AND FINANCIAL RESOURCES OF THE ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article examines and summarizes the theoretical foundations of a single social contribution in Ukraine, taking into account new legislative changes. The purpose of the article is to substantiate the theoretical basis of the single social contribution in Ukraine, as well as its reflection in the system of accounting and control over the calculations and financial resources of the enterprise. The effectiveness of the introduction of a moratorium on documentary checks of the correctness of accrual, calculation and payment of social security for the period of the legal regime of martial law and state of emergency is substantiated. The characterization of the seven stages of the social insurance system in Ukraine “Basics of the legislation of Ukraine on mandatory state social insurance” and the reorganization of the Social Insurance Fund of Ukraine and the management of its executive directorate with joining the Pension Fund of Ukraine was carried out. The expediency of electronic document circulation, the exchange of electronic primary documents with counterparties, and the preservation of an electronic archive of documents using the “SOTA” Web service were explained. The procedure for displaying a single social contribution in the system of accounting and control over calculations and financial resources of the enterprise is disclosed. In particular, the correspondence of the accounts for the calculation and payment of the single social contribution, as well as the calculation of fines and fines related to violations of the legislation of Ukraine regarding the single social contribution in the financial accounting system, is provided. In the future, further scientific research should be conducted in the direction of a clear interpretation and demarcation of various categories related to a single social contribution; improving the level of efficiency of accounting and control over receivables and payables in terms of insurance settlements and their impact on the company's financial results; increasing the efficiency of the use of the company's financial resources through the modernization of their accounting and control methods based on the application of positive practical Ukrainian and international experience.
Keywords: single social contribution, financial resources, enterprise, accounting of payments, control over resources, social taxes of developed countries, organization of electronic document circulation, public sector of the economy